Features Of The Course Of Chronic Kidney Disease According To The Degree Of Nephrinuria In A Comorbid State With Hypertension And Diabetes Mellitus. (Texas Journal of Medical Science, 2021)
According to diabetes incidence statistics for 2011, 360 million patients were registered, and by 2030 their number will reach 552 million.In recent years, when talking about comorbidity, the most discussed area in the field of internal medicine is the cardiorenal continuum. Cardiovascular diseases, obesity, type II diabetes and renal dysfunction are becoming more and more pandemics of the 21st century. In recent years, the main cause of kidney dysfunction is not its primary disease, but hypertension, that is, essential arterial hypertension (AH) and diabetes. Earlier detection of changes in podocytes and nephropathy makes it possible to diagnose and stop the process of kidney damage before the appearance of clinical signs.